Imatinib-induced dermatomyositis sine dermatitis - a rare case report - Silva, Augusto; Romão, Vasco C.; Campanilho-Marques, Raquel (Frontiers in Immunology, 2024)
Idiopathic Inflammatory Myopathies are rare conditions with several heterogeneous disease subtypes. They can range from limited muscle or skin involvement to severe, systemic, life-threatening disease. Although the etiology is unknown, some evidence suggests a role for external agents, particularly drugs. Herein, we present a case of a 71-year-old woman with chronic myeloid leukemia who developed imatinib-induced dermatomyositis sine dermatitis. The presentation was predominantly muscular, characterized by proximal muscle weakness and myalgia of the lower limbs, with positive anti-Mi2a antibodies. Spontaneous recovery was observed after drug discontinuation, without the need for immunosuppressive therapy. This is the first confirmed description of an imatinib-induced dermatomyositis sine dermatitis. It reflects the importance of a high awareness from rheumatologists and hematologists to accurately anticipate and identify similar situations.